STRATEGI PEMASARAN POTENSI WISATA ALAM GOA VERTIKAL COKRO DI DESA UMBULREJO, KECAMATAN PONJONG, KABUPATEN GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA - , MARGARITA MEGA PUSPITA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Vertical Cokro Cave is one of the natural attractions that exist in Gunungkidul, Daerah Istimewa Yogyakarta. Vertical Cokro Cave is very potential to be a tourist area especially nature tourism, due to natural beauty that is in Cokro Cave and surrounding areas. Although Goa Cokro has tourism potential that very much but can not develop withouth the support of the relevans stakeholders to asis in the development and marketing of tourism potential this. In addition to the development to be done, the manager of Cokro Cave must conduct a marketing strategy ton attract tourists to visit. The small number of vertical caves in the area of Gunungkidul, may be one of special interest tourism for the prospective tourists especially tourists of special interest tourists.